First Report of Benzoxazinoid Compounds in Woolly Cupgrass (Eriochloa villosa Thunb. Kunth), an Invasive Plant - Peter Makleit; Arnold Szilágyi; Szilvia Veres (Agronomy, 2022)
Woolly cupgrass (Eriochloa villosa Thunb. Knuth) is a common weed which is native to East Asia. It also was introduced into North America and Europe. The problems related to controlling this annual weed are due to its germination characteristics, low susceptibility to certain herbicides and considerable competitiveness against other plant species. Several genera of the Panicoideae subfamily contain benzoxazinoids, therefore we hypothesized that woolly cupgrass also produces these chemicals. To test this hypothesis, the benzoxazinoid content of plants at the flowering stage was investigated. Our results demonstrate the presence of benzoxaziniods in woolly cupgrass and this represents the first report of these compounds in this species within the Poaceae family and the Panicoideae subfamily. Benzoxazinoids likely account for the rapid spread and ecological success of woolly cupgrass in its invasive range.